Pretreatment for capacitive deionization: Feasibility tests using activated filter media and granule activated carbon filtration - Kim, Heegon; Choi, Yeseul; Lee, Soonjae; Lee, Ki-Bong; Jung, Kyung-Won; Choi, Jae-Woo (Journal of industrial and engineering chemistry (Seoul, Korea), 2021)
[Display omitted] •Novel and alternative pretreatment methods were proposed to reduce fouling in CDI•Salt removal efficiency decreased with increasing turbidity & organic matter content•Ca2+ had no noticeable effect on CDI pretreatment performance•Fe2+ and Fe3+ noticeably affected CDI electrode fouling•CDI pretreatment can be optimized as green technology to manage wastewater Dissolved organic matter and scaling are the main causes of electrode fouling, blocking activated carbon pores and reducing their performance. However, limited information exists on fouling by low molecular weight organic matter in the capacitive deionization (CDI) process. This study therefore systematically investigated for the first time a pretreatment process to prevent the accumulation of organic and inorganic matter as well as scaling in the CDI process. During various pretreatments, activated filter media and granule activated carbon were considered promising for drinking water treatment. The higher the turbidity and organic matter concentration in the CDI feed solution was, the greater the reduction of salt removal efficiency, production rate, and energy consumption became. Divalent ions, such as Ca2+, had no noticeable effect on CDI treatment performance because of the neutralization effect of the dispersant, whereas iron had a noticeable effect on CDI electrode fouling. The results of this study are foreseen to help minimize its negative impact by reducing organic matter fouling and enabling water reuse.